1993
DOI: 10.1177/014556139307200806
|View full text |Cite
|
Sign up to set email alerts
|

Tonsil and Adenoid Surgery for Airway Obstruction: Perioperative Respiratory Morbidity

Abstract: A series of 160 consecutive patients undergoing tonsil and adenoid surgery for upper airway obstruction is reported. The ages ranged from 8 months to 13 years. Sixty-seven percent were 2, 3, or 4 years of age. All were routinely admitted overnight postoperatively. Forty-five (28%) remained in the hospital longer than one night (2 to 20 days). Postoperative respiratory problems were the reason for prolonged hospital stay in 30 of these 45 patients. Preoperative “danger-signals” of potential postoperative respir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

1995
1995
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 9 publications
0
16
0
Order By: Relevance
“…However, several papers provide data pertaining to complications of surgery in children undergoing adenotonsillectomy for upper airway obstruction, all specifically addressing the risk of postoperative respiratory obstruction. [111][112][113][114][115][116][117][118] These are listed in Table 8. These authors define respiratory compromise in various ways but generally consider the need for supplemental oxygen as a minimum criterion.…”
Section: Postoperative Complications and The Need For Inpatient Monitmentioning
confidence: 99%
See 1 more Smart Citation
“…However, several papers provide data pertaining to complications of surgery in children undergoing adenotonsillectomy for upper airway obstruction, all specifically addressing the risk of postoperative respiratory obstruction. [111][112][113][114][115][116][117][118] These are listed in Table 8. These authors define respiratory compromise in various ways but generally consider the need for supplemental oxygen as a minimum criterion.…”
Section: Postoperative Complications and The Need For Inpatient Monitmentioning
confidence: 99%
“…High preoperative RDI also seems to be a risk factor for postoperative complications. 112,113 Time to onset of respiratory compromise appears to be brief, although McColley et al 112 reported that 1 patient took 14 hours to manifest respiratory symptoms.…”
Section: Postoperative Complications and The Need For Inpatient Monitmentioning
confidence: 99%
“…An RDI greater than 40, or greater than 20 with significant oxygen saturation nadir (less than 80%) has been shown to confer greater risk of adverse events. Morbid obesity itself is reported to be a high-risk comorbidity [50,54] but it not certain whether this is related to the association with OSAS or it is an independent risk factor.…”
Section: Surgical Treatmentmentioning
confidence: 99%
“…There is, however, little specific evidence for or against the use of sedatives and opioids in the perioperative period of children with OSA (11). To date, there are only anecdotal reports of respiratory depression in children in response to sedatives such as chloral hydrate (1) and respiratory depression of subjects with OSA, including children, in the perioperative period (27) including hypoxia (4,5,10,11,19,25). Ostermeier et al (24) summarized 18 cases of respiratory depression in the postoperative period for patients with OSA but included only one child, who had airway obstruction and bradycardia after chloral hydrate.…”
mentioning
confidence: 99%